2016
DOI: 10.1111/codi.13359
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of restorative proctocolectomy for ulcerative colitis by transanal total mesorectal rectal excision and single‐incision abdominal laparoscopic surgery

Abstract: Aim Laparoscopic surgery is well established for colon cancer, with defined benefits. Use of laparoscopy for the performance of restorative proctocolectomy (RPC) with ileoanal anastomosis is more controversial. Technical aspects include difficult dissection of the distal rectum and a potentially increased risk of anastomotic leakage through multiple firings of the stapler. In an attempt to overcome these difficulties we have used the technique of transanal rectal excision to perform the proctectomy. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Although no large studies have been conducted yet, a few studies have shown promising results by using ta-TME to treat UC. In a small series, Leo et al reported the outcomes of 16 patients treated with hybrid single-incision surgery combined with ta-TME for ileoanal pouch construction (20). There was only one anastomotic leak, and three cases with conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although no large studies have been conducted yet, a few studies have shown promising results by using ta-TME to treat UC. In a small series, Leo et al reported the outcomes of 16 patients treated with hybrid single-incision surgery combined with ta-TME for ileoanal pouch construction (20). There was only one anastomotic leak, and three cases with conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Leo et al [32] reported their experience of 16 total proctocolectomies and ileal pouch anal anastomoses (TPC + IPAA) for refractory mucosal ulcerative colitis using TaTME-assisted single port laparoscopy. The median operative time was 247 (185-470) min and the overall conversion rate to open surgery was 18.7%.…”
Section: Present and Futurementioning
confidence: 99%
“…A 45‐year‐old patient who had undergone subtotal laparoscopic colectomy for refractory ulcerative colitis in 2016 was scheduled for completion proctectomy with transanal total mesorectal excision (TaTME) and IPAA. Completion proctectomy with TaTME was accomplished with a combined transanal and transabdominal technique using two single ports, as previously described . The specimen was retrieved through the stoma site.…”
mentioning
confidence: 99%